Project-Based Learning with Interactive Video: Effects of Fifth-Grade Science Literacy Viewed from Self-Regulation - Sugiantara, I Putu Eka; Arnyana, Ida Bagus Putu; Gading, I Ketut (Jurnal Paedagogy, 2026)
This study aims to examine the effect of a Project-Based Learning (PjBL) model assisted by interactive video on elementary students’ science literacy, with self-regulated learning as a moderating variable in the IPAS subject. A quasi-experimental design with a pretest–posttest control group was employed. The population consisted of all fifth-grade students in Cluster IV, Sukawati District, during the 2025/2026 academic year (N = 260). The sample was selected through simple random sampling and comprised 39 students from SD Negeri 1 Batubulan Kangin and 40 students from SD Negeri 2 Batubulan Kangin. Science literacy data were collected using a test instrument, while self-regulated learning was measured using a non-test instrument. Data were analyzed using two-way analysis of variance (ANOVA) in SPSS. The results indicated that the PjBL model assisted by interactive video had a statistically significant main effect on students’ science literacy (F(1,76) = 249.416, p < 0.001). Additionally, a significant interaction effect was observed between the learning model and students’ self-regulated learning on science literacy outcomes (F(1,76) = 6.363, p = 0.015). These findings suggest that interactive video–assisted Project-Based Learning is an effective instructional approach for enhancing science literacy in elementary education.